INVESTIGATION OF IDEAS OF EASTERN THINKERS AND UNITS WITH THE SEME “ENLIGHTENMENT” (Scientific journal of the Fergana State University, 2023)
The article deals with the lexemes containing the seme “enlightenment” in the Uzbek language, their semantic subgroups, general and distinguishing features of each lexeme within the subgroups.